Electrospinning Preparation and Photocatalytic Activity of Porous TiO2 Nanofibers. (10th June 2012) - Liu, Shanhu; Liu, Baoshun; Nakata, Kazuya; Ochiai, Tsuyoshi; Murakami, Taketoshi; Fujishima, Akira
Abstract : Porous TiO2 nanofibers were prepared via a facile electrospinning method. The carbon nanospheres were mixed with the ethanol solution containing both poly(vinylpyrrolidone) and titanium tetraisopropoxide for electrospinning; and subsequent calcination of as-spun nanofibers led to thermal decomposition of carbon nanospheres, leaving behind pores in the TiO2 nanofibers. The morphology and phase structure of the products were investigated with scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD). Furthermore, the photocatalytic activity of porous TiO2 nanofibers was evaluated by photodecomposition of methylene blue under UV light. Results showed that the porous TiO2 nanofibers have higher surface area and enhanced photocatalysis activity, compared to nonporous TiO2 nanofibers.